2016
DOI: 10.1016/j.virusres.2016.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Select membrane proteins modulate MNV-1 infection of macrophages and dendritic cells in a cell type-specific manner

Abstract: Noroviruses cause gastroenteritis in humans and other animals, are shed in the feces, and spread through the fecal-oral route. Host cellular expression of attachment and entry receptors for noroviruses is thought to be a key determinant of cell tropism and the strict species-specificity. However, to date, only carbohydrates have been identified as attachment receptors for noroviruses. Thus, we investigated whether host cellular proteins play a role during the early steps of norovirus infection. We used murine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Binding of the MNoV-1 particles pretreated with PBS(-)+EDTA (pH 8) to RAW264.7 cells, however, showed no significant difference from those pretreated with DMEM (Left bars in S2A Fig ). RAW264.7 cells are known to express several molecules involved in MNoV adsorption [ 21 ]. In contrast, HEK293T cells genetically expressing CD300lf (HEK293T/CD300lf cells) can adsorb MNoV particles on the cell surface via direct interaction with the CD300lf [ 22 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Binding of the MNoV-1 particles pretreated with PBS(-)+EDTA (pH 8) to RAW264.7 cells, however, showed no significant difference from those pretreated with DMEM (Left bars in S2A Fig ). RAW264.7 cells are known to express several molecules involved in MNoV adsorption [ 21 ]. In contrast, HEK293T cells genetically expressing CD300lf (HEK293T/CD300lf cells) can adsorb MNoV particles on the cell surface via direct interaction with the CD300lf [ 22 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Lastly, there may be cell type-specific inhibitors of MNV entry which can interact with I/LnJ CD300LF but not with C57BL/6J CD300LF. A recent study into critical factors for entry of MNV into macrophages and dendritic cells identified several proteins, including CD98 and CD36, that influence attachment and could potentially fulfill such a role ( 46 ). All these three possibilities are plausible, and future studies will investigate these possibilities and attempt to identify this modulatory factor(s).…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous work demonstrating that OMVs from other commensal bacteria can enter cells and subsequently influence cellular responses ( 43 – 45 ), we examined the ability of OMVs from E. cloacae and B. thetaiotaomicron to enter RAW264.7 cells. In addition, since MNV has been shown to infect macrophages as early as 1 hpi, which is the standard incubation timepoint for MNV infection assays ( 26 , 28 ), we tested if OMVs were capable of entering macrophages within the same time frame. To do this, RAW264.7 macrophages were inoculated with DiO-labeled OMVs, and the cells were visualized after 1 hr of inoculation with fluorescent microscopy.…”
Section: Resultsmentioning
confidence: 99%